2018
DOI: 10.1038/s41598-018-21892-y
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial Organization of the Gastrointestinal Microbiota in Urban Canada Geese

Abstract: Recent reviews identified the reliance on fecal or cloacal samples as a significant limitation hindering our understanding of the avian gastrointestinal (gut) microbiota and its function. We investigated the microbiota of the esophagus, duodenum, cecum, and colon of a wild urban population of Canada goose (Branta canadensis). From a population sample of 30 individuals, we sequenced the V4 region of the 16S SSU rRNA on an Illumina MiSeq and obtained 8,628,751 sequences with a median of 76,529 per sample. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 47 publications
(79 reference statements)
3
32
3
Order By: Relevance
“…[32]. Contrary to our results, Canada geese (Branta canadensis) harboured a higher bacterial diversity in their lower than upper GIT [33]. However, we did detect a similar low diversity in the small intestine in our study as in the duodenum of Canada geese [33] and in the ileum of Ostriches (Struthio camelus) [34].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[32]. Contrary to our results, Canada geese (Branta canadensis) harboured a higher bacterial diversity in their lower than upper GIT [33]. However, we did detect a similar low diversity in the small intestine in our study as in the duodenum of Canada geese [33] and in the ileum of Ostriches (Struthio camelus) [34].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our results, Canada geese (Branta canadensis) harboured a higher bacterial diversity in their lower than upper GIT [33]. However, we did detect a similar low diversity in the small intestine in our study as in the duodenum of Canada geese [33] and in the ileum of Ostriches (Struthio camelus) [34]. The small intestine is thought to be the gut section that supports the least microorganisms, due to its high concentration of enzymes [35] and the low pH in the anterior section: the gizzard [36].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies on wild birds have demonstrated low bacterial diversity and community composition differences in the midgut region (stomach and small intestine) compared to the crop microbiota. This suggests that the highly-acidic conditions in the midgut region acts as a barrier for environmental and foodborne bacteria [14,66,76,77]. This is further evident when we look at previously published mealworm gut microbiomes [78], where only a small fraction of the microbiome consists of bacterial genera that we identi ed in the gut microbiomes of mealworm-fed P. major.…”
Section: P Major Gut Microbiomes Respond To Diet Changes But Not Asmentioning
confidence: 74%
“…The seed diet led to a signi cant increase in relative abundance of the genera Fusobacterium (Fusobacteria), Blautia (Firmicutes), and Ruminococcus (Firmicutes). Some Fusobacterium members are animal pathogens [63], but their consistent presence in wild bird guts [2,14,64,65], especially in herbivorous species [64][65][66], suggests a possible symbiotic role. Bacteria from the genus Blautia may facilitate the metabolism of plant secondary metabolites [67,68], consistent with an increase in the relative abundance of this genus in birds feeding on seeds.…”
Section: P Major Gut Microbiomes Respond To Diet Changes But Not Asmentioning
confidence: 99%
“…Replicate samples from a single intestine were sequenced to elucidate the microvariation that occurs within the intestine. Variation in microbiota between discrete organs of the gastrointestinal tract has been demonstrated in diverse taxa e.g., in snakes (Colston, Noonan, & Jackson, 2015), in humans (Costello et al, 2009), in geese (Drovetski et al, 2018), in alligators (Keenan, Engel, & Elsey, 2013), and in teleost fish (Pratte, Besson, Hollman, & Stewart, 2018). However, few studies have looked at the variation within a single organ.…”
Section: Sample Versus Pcr Replicatesmentioning
confidence: 99%